The marsh demon - Hulme-Cross, Benjamin (Hulme-Cross, Benjamin. Dark Hunter., 2015)
When Mr. Blood and his young assistants, Edgar and Mary, are called to a village that is terrorized once a year by a monster, the children are forced to serve as bait.